Biosyntheses characterization of alkaloids and flavonoids in Sophora flavescens by combining metabolome and transcriptome - Guangfei Wei (Nature Portfolio, 2021)
Abstract Sophora flavescens are widely used for their pharmacological effects. As its main pharmacological components, alkaloids and flavonoids are distributed in the root tissues wherein molecular mechanisms remain elusive. In this study, metabolite profiles are analyzed using metabolomes to obtain biomarkers detected in different root tissues. These biomarkers include alkaloids, phenylpropanoids, and flavonoids. The high-performance liquid chromatography analysis results indicate the differences in principal component contents. Oxymatrine, sophoridine, and matrine contents are the highest in the phloem, whereas trifolirhizin, maackiain, and kushenol I contents are the highest in the xylem. The transcript expression profiles also show tissue specificity in the roots. A total of 52 and 39 transcripts involved in alkaloid and flavonoid syntheses are found, respectively. Among them, the expression levels of LYSA1, LYSA2, AO2, AO6, PMT1, PMT17, PMT34, and PMT35 transcripts are highly and positively correlated with alkaloids contents. The expression levels of 4CL1, 4CL3, 4CL12, CHI5, CHI7, and CHI9 transcripts are markedly and positively correlated with flavonoids contents. Moreover, the quantitative profiles of alkaloids and flavonoids are provided, and the pivotal genes regulating their distribution in S. flavescens are determined. These results contribute to the existing data for the genetic improvement and target breeding of S. flavescens.